Key Tradeoffs Limiting the Performance of Organic Photovoltaics. Issue 28 (17th May 2018) - Ramirez, Ivan; Causa', Martina; Zhong, Yufei; Banerji, Natalie; Riede, Moritz
Abstract: 2017 saw the publication of several new material systems that challenge the long‐held notion that a driving force is necessary for efficient exciton dissociation in organic photovoltaics (OPVs) and that a loss of ≈0.6 eV between the energy of the charge transfer state E ct and the energy corresponding to open circuit is general. In light of these developments, the authors combine insights from device physics and spectroscopy to review the two key tradeoffs limiting OPV performances. These are the tradeoff between the charge carrier generation efficiency and the achievable open circuit voltage ( V oc ) and the tradeoff between device thickness (light absorption) and fill factor. The emergence of several competitive nonfullerene acceptors (NFAs) is exciting for both of these. The authors analyze what makes these materials compare favorably to fullerenes, including the potential role of molecular vibrations, and discuss both design criteria for new molecules and the achievable power conversion efficiencies. Abstract : Organic photovoltaics have made astounding progress both in fundamental understanding and device performance. In particular, nonfullerene acceptors bring into question previous empirical estimates of the achievable power conversion efficiencies. This report aims to provide a perspective on the physics underlying the conventional and new systems and their performance limits.